IMPLEMENTATION OF VERTICAL COMMUNICATION BETWEEN LEADERS AND SUBORDINATES IN BUILDING HARMONIOUS RELATIONSHIPS AT THE ULIL ALBAB AMIL ZAKAT INSTITUTION - Melja Ramdhan; Azhar Azhar (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
This study investigates the implementation of vertical communication between organizational leaders and subordinates as a mechanism for building and sustaining harmonious working relationships within the Ulil Albab Amil Zakat Institution, Medan. Grounded in organizational communication theory, the research examines both downward communication (from leaders to subordinates) and upward communication (from subordinates to leaders) as complementary dimensions of an integrated communicative process. Employing a descriptive qualitative approach through in-depth interviews, direct observation, and documentation, the study reveals that vertical communication at the institution is characterized by openness, transparency, motivational leadership, and constructive feedback. Leaders demonstrate exemplary conduct and responsiveness to employee aspirations, while subordinates exhibit accountability and proactive participation. Minor barriers related to generational differences and perceptual divergence were identified but are effectively managed through direct dialogue. The findings affirm that harmonious organizational relationships emerge not spontaneously but through the deliberate cultivation of balanced, two-way vertical communication channels that affirm individual dignity, foster mutual trust, and align collective effort with institutional vision and mission.